Enhancing Santri Entrepreneurship through University–Pesantren Engagement - Purnamasari, Imas; Machmud, Amir; Nugraha, Nugraha; Ramdhany, Muhamad Arief; Lhutfi, Iqbal; Mulyadi, Hari; Sojanah, Janah; Supardi, Endang; Rasto, Rasto; Istikomah, Navik (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
This study examines a community engagement initiative aimed at enhancing the entrepreneurial competencies of santri at an Islamic boarding school in West Java, Indonesia. The programme was implemented on 1 November 2025 and involved more than 200 santri. Employing an experiential learning approach, the intervention consisted of interactive training sessions, Business Model Canvas workshops, and experience-sharing activities with successful entrepreneurs who were alumni of Islamic boarding schools. The instructional content covered fundamental entrepreneurship concepts, development of the entrepreneurial mindset, opportunity identification, digital marketing, basic financial management, and Islamic entrepreneurship principles. Pre-test results indicated that 65% of participants had a limited understanding of entrepreneurship, whereas post-test findings revealed substantial improvement, with 85% demonstrating a comprehensive understanding of core entrepreneurial concepts.